Essentials of systems analysis and design / Joseph S. Valacich, Joey F. George, Jeffrey A. Hoffer - Valacich, Joseph S.
PART I: FOUNDATIONS FOR SYSTEMS DEVELOPMENT Chapter 1. The Systems Development Environment Chapter 2. The Sources of Software Chapter 3. Managing the Information Systems Project PART II: SYSTEMS PLANNING AND SELECTION Chapter 4. Systems Planning and Selection PART III: SYSTEMS ANALYSIS Chapter 5. Determining System Requirements Chapter 6. Structuring System Requirements: Process Modeling Chapter 7. Structuring System Requirements: Conceptual Data Modeling PART IV: SYSTEMS DESIGN Chapter 8. Designing the Human Interface Chapter 9. Designing Databases PART V: SYSTEMS IMPLEMENTATION AND OPERATION Chapter 10. Systems Implementation and Operation